2019
DOI: 10.1130/g46250.1
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of depleted continental mantle by subduction and plumes at the Hikurangi Plateau large igneous province, southwestern Pacific Ocean

Abstract: Seismic reflection and refraction data from Hikurangi Plateau (southwestern Pacific Ocean) require a crustal thickness of 10 ± 1 km, seismic velocity of 7.25 ± 0.35 km/s at the base of the crust, and mantle velocity of 8.30 ± 0.25 km/s just beneath the Moho. Published models of gravity data that assume normal crust and mantle density predict 5–10-km-thicker crust than we observe, suggesting that the mantle beneath Hikurangi Plateau has anomalously low density, which is inconsistent with previous suggestions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 40 publications
8
33
1
Order By: Relevance
“…Recent seismic surveys confirmed that the crust is over 10 km thick, and its thickness gradually increases from north to south in accordance with the latitudinal variation in seafloor depth (Kodaira et al, 2018;Mochizuki et al, 2019). In the northern part of the plateau where the seafloor is deeper (>3,000 m), more seamounts emerge on the seafloor, but the southern part of the plateau also hosts a number of basement highs that are buried by thick sediments (Kodaira et al, 2018;Mochizuki et al, 2019). Correspondingly, the thickness of the trench-fill sediments varies significantly along the trench from approximately 1 km in the north to >5 km in the south, which drives a progressive increase in the magnitude and extent of frontal accretion along the margin (Barnes et al, 2010).…”
Section: Geological Settingmentioning
confidence: 69%
See 2 more Smart Citations
“…Recent seismic surveys confirmed that the crust is over 10 km thick, and its thickness gradually increases from north to south in accordance with the latitudinal variation in seafloor depth (Kodaira et al, 2018;Mochizuki et al, 2019). In the northern part of the plateau where the seafloor is deeper (>3,000 m), more seamounts emerge on the seafloor, but the southern part of the plateau also hosts a number of basement highs that are buried by thick sediments (Kodaira et al, 2018;Mochizuki et al, 2019). Correspondingly, the thickness of the trench-fill sediments varies significantly along the trench from approximately 1 km in the north to >5 km in the south, which drives a progressive increase in the magnitude and extent of frontal accretion along the margin (Barnes et al, 2010).…”
Section: Geological Settingmentioning
confidence: 69%
“…Subducting along the Hikurangi Trough is the Hikurangi Plateau, a large igneous province of Cretaceous age with a crustal thickness over 10 km (Davy et al, 2008; Mochizuki et al, 2019). The structure of the incoming Hikurangi Plateau is different from typical oceanic crust and is characterized by thick low‐velocity layers that shows a gradual increase in Vp with depth from ~1.6 km/s at the seafloor to ~5.0 km/s at 4‐km depth below seafloor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our V P model provides new wide-angle seismic constraints on the velocity structure and thickness of the Hikurangi Plateau at the northern Hikurangi margin that can be compared with recent studies along the southern Hikurangi margin (Figure 1a; SAHKE and PEGASUS). Offshore Gisborne, the Hikurangi Plateau is 9 + 1.6/−2.3 km thick, which is slightly thinner than the results of Mochizuki et al (2019; 10 ± 1 km) along the SAHKE transect to the south, and much thinner than the findings of Herath et al (2020; 12 ± 1 km) along the southern Hikurangi margin offshore Wairarapa (Figure 1a). Barker et al 2018), 1947 tsunami earthquake epicenters (Downes et al, 2017), and slip contours (cm) from a 2014 slow slip event recorded with seafloor pressure gauges (Wallace et al, 2016).…”
Section: Crustal Structure Of the Hikurangi Plateaumentioning
confidence: 71%
“…We compare the results of our P‐wave velocity‐depth and gravity models with other observations of the extent of the Hikurangi Plateau and adjacent oceanic crust beneath the Chatham Rise and southern Zealandia region (Figure 6). The 10 km thickness of the Hikurangi Plateau underlying the Chatham Rise implied by our P‐wave velocity‐depth model along profile AWI‐20160400 is in very good agreement with thicknesses between 10 and 12 km derived from (i) gravity models along HKDC‐1 line (Figure 7; Davy et al, 2008); (ii) the AWI‐20160100 seismic refraction profile east of the Chatham Islands (Figure 6c; Riefstahl et al, 2020); and (iii) seismic refraction profiles from the northern Hikurangi margin east of the North Island (Figure 7; Henrys et al, 2013; Herath et al, 2020; Mochizuki et al, 2019, Scherwath et al, 2010; Tozer et al, 2017). The available data from the Hikurangi Plateau do not suggest large variations in thickness along the Chatham Rise between 175°E to 176°W.…”
Section: Discussionmentioning
confidence: 99%